2014
DOI: 10.1021/nl503057g
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Near-Infrared High-Q Perovskite Whispering-Gallery Planar Nanolasers

Abstract: Near-infrared (NIR) solid-state micro/nanolasers are important building blocks for true integration of optoelectronic circuitry. Although significant progress has been made in III-V nanowire lasers with achieving NIR lasing at room temperature, challenges remain including low quantum efficiencies and high Auger losses. Importantly, the obstacles toward integrating one-dimensional nanowires on the planar ubiquitous Si platform need to be effectively tackled. Here we demonstrate a new family of planar room-tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
765
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 750 publications
(788 citation statements)
references
References 29 publications
(63 reference statements)
18
765
4
1
Order By: Relevance
“…The inset shows a photograph of a converted chip 6 . e, an optical image of CH3NH3PbI3 platelets prepared by vapor phase synthesis 7 . f, SEM image of a SiO2 microsphere conformally coated with CH3NH3PbI3 via atomic layer deposition 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The inset shows a photograph of a converted chip 6 . e, an optical image of CH3NH3PbI3 platelets prepared by vapor phase synthesis 7 . f, SEM image of a SiO2 microsphere conformally coated with CH3NH3PbI3 via atomic layer deposition 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, HPVKs layers have been successfully applied in a wide range of photonic devices, such as photodetectors [91,92] or light emitting diodes [90,93]. In addition, since HPVKs present a fast carrier formation and long recombination time, they are promising materials to reduce the stimulated emission threshold in active devices [94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109], as it has been nicely reviewed in [90].…”
Section: -P14mentioning
confidence: 99%
“…Zhang et al synthetized triangular and hexagonal CH 3 NH 3 PbI 3 fabricated from PbI 2 nanoplatelets by a chemical vapor depositing technique (see Fig. 15d) [100]. The dimensions of the polygon were an edge length between 5 and 50 μm, a thickness of 20-300 nm wide and an angle between edges of 60 and 120 • , consistent with the perovskite lattice.…”
Section: -P14mentioning
confidence: 99%
“…These excellent properties, along with their high quantum yield and wavelength tunability, make halide perovskites ideal for light‐emission applications such as for light‐emitting diodes (LEDs), light‐emitting field‐effect transistors, and lasing 13, 14, 15, 16, 17, 18, 19. Since the first demonstration of ultrastable amplified spontaneous emission (ASE) with broad spectral tunability from perovskite thin films and lasing from perovskite crystals,20 perovskite lasing in a broad range of cavity structures, including microplatelets,21 nanowires,22 microspheres,23 and distributed Bragg reflection (DBR) mirrors,24 have been realized 25. Notably, Zhu et al recently reported a solution‐processed technique to synthesize single‐crystal perovskite nanowires and demonstrated their application on lasers with high‐quality factor and low lasing threshold 26.…”
Section: Introductionmentioning
confidence: 99%